Strategic spending in federal governments: Theory and evidence from the US - Pablo J. Garofalo (Journal of Applied Economics, 2019)
Past research on the allocation of federal resources to localities has failed to account for the interaction between federal and state governments. Here a sequential-move game of such interaction is developed, where state governments behave like political surrogates for the federal government when they are politically aligned, while they engage in political competition when not. The model predicts that aligned states increase the funding of aligned localities, while the federal government increases the funding of aligned localities only within nonaligned states. Using data from the Census of Governments 1982-2002 and a difference-in-difference strategy reveals that such predictions are upheld by the data. My findings find a limit to the benefits of decentralization. Although the standard view is that it removes political power from the center, I find that decentralization could concentrate such power more at local level, which may give the President political advantages within unaligned states through aligned localities.
Keywords: 330; Government spending; political alignment; political competition; strategic interaction